PELAKSANAAN SISTEM MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (SMK3) BERDASARKAN OHSAS 1800: 2007 PADA UNIT SPINNING V PT. SINAR PANTJA DJAJA (PT. SPD) DI SEMARANG TAHUN 2014 (Universitas Negeri Semarang (UNNES) in cooperation with Association of Indonesian Public Health Experts (Ikatan Ahli Kesehatan Masyarakat Indonesia (IAKMI)), 2015)
The object of this research in PT. SPD Semarang by using the type and design was qualitative and descriptive research the were aims to know the execution of SMK3 application on OHSAS 18001: 2007 in PT. SPD Semarang. From the results show that implementation of SMK3 on OHSAS PT. SPD as much as 131 points (87,3%). For points that haven’t met the standards yet as much as 10 points (6.7%). And for the points which don’t meet as many as 9 points (6%). So, PT. SPD were included in the category level assessment good or equivalent certificate flag gold tally. It was advisable to PT. SPD to enhance the application of SMK3 based on OHSAS with: (1) required to have a manual SMK3 on OHSAS, (2) required to have procedures for identifying, accessing and updating rules K3, (3) required to provide competent resources to SMK3 implementations, (4) the HSE training should be distinguished the responsibilities, competencies, languages, skills and risk, (5) should be doing simulated fire emergency, (6) must have data calibration tools in accordance with the regulations.